Exploring the spatiotemporal dynamics and coupling coordination of urbanization and habitat quality in the Yangtze river basin, China - Wu, Jianfeng; Guo, Zhongyang; Luo, Guangjie; Zhang, Fengtai; Chen, Jingpeng; Li, Wei; Chen, Qiwei; Liao, Jingjing; Cao, Guangjie (Frontiers in Environmental Science, 2024)
Rapid urbanization induces significant changes in land use, exerting a profound impact on regional habitat quality. Understanding the interconnectedness of urbanization and habitat quality is crucial for safeguarding the regional ecological environment and promoting sustainable urban development. Cities along the Yangtze River, as the core region of the Yangtze River Economic Belt in China, serve as a typical and critically important area to investigate the dynamic response of habitat quality to rapid urbanization. This study employs the InVEST model and entropy method to assess the spatiotemporal dynamics of habitat quality and urbanization in Yangtze River cities. Using the coupling coordination degree model, it analyzes the interplay between urbanization and habitat quality, elucidating dynamic response patterns and emphasizing the need for pertinent policy measures. Our findings reveal that from 1990 to 2019, urbanization levels in the study area surged by over six times, while habitat quality consistently declined, reflecting a 4.5% decrease. Notably, spatial variances were observed along the upstream, midstream, and downstream segments of the river. Although an inverse relationship between urbanization and habitat quality predominates, three cities demonstrated a positive correlation. The study also indicates a stable increase in the coupling coordination degree between urbanization and habitat quality, evolving from a phase of urbanization lag to one of synchronization followed by habitat quality lag. Among the cities, Chongqing emerges as an exemplary model for the coordinated development of urbanization and habitat quality. These insights provide a theoretical foundation and policy guidance for enhancing sustainable urban and ecological strategies in the region.